Prevalence and severity of dental fluorosis in students from a public school in a region of northern Peruvian - Odiaga Lopez, Diana Carolina (2025)
Objective: To determine the prevalence and severity of dental fluorosis in students attending a public school in a northern Peruvian region Material and methods: The study was cross-sectional and descriptive. The sample consisted of 161 students aged 6 to 12 years. A previously trained and calibrated researcher performed clinical evaluation to record the presence of dental fluorosis using a general data collection form. The presence of dental fluorosis was diagnosed using the Dean Index. Descriptive and inferential data analysis was performed, and the chi-square test was used. Results: A high prevalence of dental fluorosis was found (80.7%). Most of male students (76.2%) presented dental fluorosis, compared to female students (23.8%). Most affected students were 7-year-olds (73.1%), and by severity, it was moderate for both sexes. Conclusion: TThe prevalence of dental fluorosis among the students evaluated was high, with a predominance of moderate severity. Furthermore, male students and students aged 7 years had a higher prevalence of dental fluorosis.